The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1017/s136672890100044x
|View full text |Cite
|
Sign up to set email alerts
|

Gender assignment and gender agreement in advanced French interlanguage: a cross-sectional study

Abstract: An analysis of 519 gender errors (out of 9,378 modi®ers) in the advanced French interlanguage of 27 Dutch L1 speakers con®rms earlier ®ndings that gender assignment and/or agreement remain problematic for learners at all levels. A hypothesis derived from Pienemann's Processability Theory (1998a) that accuracy rates would be higher for gender agreement in structures involving no exchange of grammatical information between constituents was not con®rmed. The analysis of interindividual and intra-individual variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
110
1
10

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(135 citation statements)
references
References 68 publications
12
110
1
10
Order By: Relevance
“…The same pattern emerged in the data of Bartning's (2000b) started using the strategy of overgeneralisation of the masculine gender" (2000b: 231). Dewaele and Véronique (2001) also found that gender errors most often involved the misuse of masculine for feminine gender: 73.5 percent of determiners and 63 percent of adjectives with incorrect gender were masculine forms (p. 285). This increased use of masculine gender for feminine nouns in French interlanguage has been noticed before (Carroll 1989;Bartning 1999).…”
Section: Gender In L2 Frenchmentioning
confidence: 94%
See 2 more Smart Citations
“…The same pattern emerged in the data of Bartning's (2000b) started using the strategy of overgeneralisation of the masculine gender" (2000b: 231). Dewaele and Véronique (2001) also found that gender errors most often involved the misuse of masculine for feminine gender: 73.5 percent of determiners and 63 percent of adjectives with incorrect gender were masculine forms (p. 285). This increased use of masculine gender for feminine nouns in French interlanguage has been noticed before (Carroll 1989;Bartning 1999).…”
Section: Gender In L2 Frenchmentioning
confidence: 94%
“…The author concluded that a dissociation seems to exist between processing and grammatical knowledge, with the latter lagging behind. Dewaele and Véronique (2001) analyzed gender errors in the preadvanced to advanced oral French interlanguage of 27 L1 Dutch speakers who were university students in Brussels. The authors focused on interindividual and intra-individual variation in gender accuracy rates.…”
Section: Gender In L2 Frenchmentioning
confidence: 99%
See 1 more Smart Citation
“…De manière générale, les résultats des études disponibles en acquisition L1 et en psycholinguistique sont univoques dans le constat que la maîtrise du GG débute tôt chez des enfants monolingues et bilingues de langue maternelle française (Carroll 1989, Tipurita & Jean 2014Guillard-Chamart 2009, Granfeldt 2005, Dewaele & Véronique 2001, Holmes et al 1999. La recherche de Karmiloff-Smith (1979) démontre que dès l'âge de trois ans, un locuteur natif (LN) francophone exploite inconsciemment les régularités formelles dans l'assignation ; ce constat est corroboré par Mills (1986) pour les LN germanophones, dans une étude sur des enfants âgés de 5 et 6 ans.…”
Section: Acquisition Du Gg En L1 Et Fl2unclassified
“…Des locuteurs natifs anglophones, au contraire, « transfer their noun-category, crucially without an inherent gender feature, to the task of acquiring new words » (Carroll 1989: 581). Par conséquent, ils les dissocieraient des déterminants et les associeraient à des unités phonologiques indépendantes en utilisant quelques règles heuristiques apprises par coeur (Dewaele & Véronique 2001). La stratégie du suremploi serait donc moins exploitée par des locuteurs L1 d'une langue avec GG.…”
Section: Effet De La L1 Dans L'assignation Excessive Du Masculin En Fl2unclassified